Jaminan Informasi dan Keamanan yang Lebih Baik: Studi Kasus BPJS Kesehatan - Abdul Hakim Satria Nusantara; Irhan Kahirul Umam; Muharman Lubis (NUANSA INFORMATIKA, 2024)
In 2021, BPJS Kesehatan experienced a significant data leak incident, where the personal data of 279 million Indonesians was leaked and traded on hacker forums. This incident has a serious impact on individual privacy and the reputation of BPJS Kesehatan. This paper analyzes the incident using the security lifecycle method, which consists of the stages of identification, analysis/assessment, protection, and monitoring. The findings suggest that weaknesses in IT security systems and a lack of continuous monitoring contributed to the leaks. Recommendations include strengthening security protocols, staff training, and implementing real-time monitoring to prevent similar incidents in the future.